Hooked on Hooks? A Study in the Utilization of Skin Hooks. Issue 1 (January 2019) - Clark, Summer; Truong, Valerie; Stasko, Thomas
Abstract : BACKGROUND: The skin hook is a valuable instrument used in the practice of dermatologic surgery. However, because of numerous factors, the degree of its use varies extensively. OBJECTIVE: The purpose of this study was to examine practice trends among dermatologic surgeons regarding the use of skin hooks, as well as analyze factors influencing their use. METHODS: A survey comprising 14 questions was distributed to members of the American College of Mohs Surgery and the American Society for Dermatologic Surgery. Results were recorded, and statistical analysis was conducted using the 2-sample z -test to compare 2 population proportions. RESULTS: Five hundred seventy-one responses were received, with comments. 85.1% of respondents reported using skin hooks. Their use was further characterized as minimal (20.7%), moderate (29.0%), and extensive (35.4%). The utilization of skin hooks was additionally categorized based on age, gender, fellowship training, number of years in practice, practice setting, and history of experience/observance of a sharps exposure. Only the presence or absence of fellowship training demonstrated a statistically significant difference in the use of skin hooks. CONCLUSION: Skin hooks are highly used tools among dermatologic surgeons. Their use requires appropriate training and experience, and care must be taken to minimize risk of exposure.